A facile noncatalytic methyl ester production from waste chicken tallow using single step subcritical methanol: Optimization study. (28th August 2019) - Santosa, Felix Harijaya; Laysandra, Livy; Soetaredjo, Felycia Edi; Santoso, Shella Permatasari; Ismadji, Suryadi; Yuliana, Maria
Summary: In this modern era, an increase in urbanization causes the escalating trend of fuel demand as well as environmental pollution problems. Various biofuels research with the respect of climate change and emission reduction recently intensifies, particularly in biodiesel. In Indonesia, diesel oil currently in use contains 20% of biodiesel. Utilizing waste‐based resources such as rendered chicken tallow as the feedstock could be the solution to both energy and environmental challenges. However, chicken tallow contains a significant amount of free fatty acid (FFA) which will obstruct the production yield of biodiesel. In this study, catalyst‐free subcritical methanol has been employed to convert waste chicken tallow (WCT) with high FFA into biodiesel. Design of experiment was conducted to study the effect of temperature, time, and the molar ratio of methanol to fats on the purity and recovery of fatty acid methyl esters (FAMEs). Based on the optimization study performed by response surface methodology (RSM), all three independent variables gave a significant effect on the recovery of FAME. From the experimental results, the maximum FAME yield obtained was 98.43 ± 0.22% with the optimum condition as follows: 167°C, 36.8 minutes, and 42.7:1 (methanol/WCT, mol/mol), while the predicted FAME yield obtained using RSM was 97.76%. The methyl ester composition of WCT‐based biodiesel ranges from C13 to C24. Abstract : Waste chicken tallow has been successfully transformed to biodiesel with high recovery using a facile transesterification technique of single step subcritical methanol. Process optimization using RSM and three‐way ANOVA has been effectively employed; 98.43 ± 0.22% FAME recovery with 97.17% purity was obtained in this noncatalytic process, with the optimum operating condition of 167°C, 36.8 minutes, molar ratio of methanol to WCT 42.7:1. Subcritical methanol can be applied to utilize waste chicken tallow to replace the conventional process.